SYSTEMATIC LITERATURE REVIEW : IMPROVING CONNECTION SKILLS STUDENT MATHEMATICS USING REACT STRATEGY - Shafira, Nabilah Aulia; Waluya, Budi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
One of the main or basic abilities for students in the process of learning mathematics is the ability of mathematical connections. The purpose of this study is to find out the effect of improving students' mathematical connection skills with the REACT strategy from 2015 to 2024. The research method uses Systematic Literature Review (SLR) using the PRISMA method on all research articles based on Google Scholar and SCIMAGOJR The search procedure uses selection criteria and includes the influence of variables, namely year of publication, level of education, and research material. The results showed that there was an increase in students' mathematical connection skills with the REACT strategy.